Quorum quenching: A key biological activity of marine actinobacteria extracts for acne vulgaris control - María Clara De La Hoz-Romo; Luis Díaz; Javier Gómez-León; Luis Felipe Reyes; Marynes Quintero; Luisa Villamil (Biotechnology Reports)
Quorum sensing (QS) regulates virulence factors in bacteria associated with acne vulgaris. Consequently, extracts from marine actinobacteria sourced from Colombian Caribbean sponges and octocorals were screened for quorum quenching (QQ) and anti-biofilm activity. The most promising extract, G12.218 from Promicromonospora sp. CLIVUS-G12218, inhibited QS by 97 % via AI-2 signaling in Vibrio harveyi BB170 and reduced Staphylococcus aureus biofilm by 60 % at 3 mg/L, without cytotoxicity to keratinocytes and fibroblasts.Untargeted metabolomics of QQ active and non-active extracts revealed distinct profiles enriched in terpenoids, phenols, and butenolides, potentially linked to bioactivity. These extracts also exhibited antioxidant capacity (18 ± 0.23 µmol TE/L) and hyaluronidase inhibition up to 72.8 %, suggesting skin-protective properties. These findings highlight the potential of marine actinobacteria as a source of QQ and anti-biofilm agents for acne therapy and skincare.